The internal and external influences on U.S. policy in the Middle East - Chahine, Tarek Jarjoura (Journal of Economic, Administrative and Legal Sciences, 2025)
This study examines how U.S. policy in the Middle East is influenced by internal factors such as its secure geographical location, natural resources, demographic diversity, political system, and military and scientific capabilities, all of which grant it flexibility and independence in decision-making. The personality of the U.S. president also plays a significant role in shaping the approach to the region. Externally, Washington seeks to maintain its global dominance in the face of challenges such as China's rise and Russia's resurgence, while also considering the interests of its European allies. Regional factors and challenges—such as terrorism and sectarian conflicts—serve to justify American intervention under the pretext of ensuring stability. Moreover, support for Israel and engagement with Turkey are key components in shaping U.S. policies in the region. And the study aimed to qualitatively analyze the interaction between internal and external factors in shaping U.S. policy in the Middle East, employing a descriptive-analytical methodology.
Keywords: Internal and external American influences; U.S. policy; Middle East; international system